Geochemical modeling in the evaluation of ore-forming potential of magmatic-hydrothermal systems - S.E. Shnyukov; I.I. Lazareva; V.S. Portnov; A.G. Aleksieienko; L.I. Gavryliv; D.K. Makat; A.G. Maratova (Қарағанды университетінің хабаршысы. Физика сериясы)
Quantitative geochemical modeling possibilities of ore-bearing aqueous fluids separation process from a magmatic melt are considered. Suggested procedures allow calculation of fluid/melt distribution coefficient values for trace elements, their contents in a fluid, as well as its total resources in a genetically related metasomaticaly altered rocks. Application of this approach to the geochemical modeling of real oregenerating magmatic-hydrothermal system of the Korosten pluton granitoids (Ukrainian Shield), and associated hydrothermal-metasomatic formations (Suschano-Perzhanskaya area) has confirmed its efficiency. The purpose of present and future research is to obtain estimations of Ukraine and Kazakhstan regions mineral resources potential independent from a simple summation of previously conducted regional works.